Lake Eyre - Australia Post. ([Melbourne] : Australia Post, 2011)
Colour lithographic poster advertising a series of stamps and associated products issued to capture the unique landscape of Lake Eyre and its vast and changing environment. Lake Eyre is the centre of the vast Lake Eyre Basin located 700km north of Adelaide in the deserts of central Australia. During the dry season Lake Eyre is primarily characterised by great salt pans, however the recent high rainfall in 2011, has filled the vast floodplains around Lake Eyre creating wetlands brimming with life. Pelicans have returned to rivers and waterholes all around Lake Eyre to breed. Images of the four stamps are inset across the top of the poster against a pale blue background. Below this is an image of pelicans standing at the edge of Lake Eyre.
Caption title.
Keywords: Australia Post -- Posters; Landscapes on postage stamps -- Posters; Birds on postage stamps -- Posters; Postage stamps -- Australia -- Posters; Posters, Australian; Eyre, Lake, Basin -- On postage stamps -- Posters; Australia -- On postage stamps -- Posters; Australian